Development of a Quantitative Method for Monitoring 2-Mercaptobenzothiazole Based on Isotopic Iodoacetamide and Tandem MS - Liang, Shih S.; Shen, Po Tsun; Shiue, Yow Ling; Chang, Yu-Tzu; Sung, Pei (Current Analytical Chemistry, 2020)
Background: MBT, a rubber accelerator, was popularly used in rubber manufacturing. However, the experts from the International Agency for Research on Cancer suggested that MBT was listed in Group 2A carcinogenic material. Methods: Therefore, we developed a quantification method based on LC-QqQ-MS/MS, using isotopic iodoacetamide and 13C2, D2-iodoacetamide to react with the thiol group on MBT to generate the iodoacetamide-modified MBT as a standard for a calibration curve and the 13C2, D2-iodoacetamidemodified MBT analog as an internal standard. Results: Using LC-QqQ-MS/MS, we explored a Multiple Reaction Monitoring (MRM) MS detection mode by detecting m/z of precursor and product ions of MBT, and this method was validated using linear range, LOD, LOQ, intra-day, inter-day, and average recoveries. This validated method was successfully applied to a waste tire as a real sample. Conclusion: By a complete synthesis with isotopic iodoacetamide alkylation, MBT could be modified with iodoacetamide and 13C2, D2-iodoacetamide with high yields. Furthermore, in MS detection, the signal enhancement could be observed clearly after alkylation. Therefore, this modification of MBT with isotopic iodoacetamide vastly improved the detection of MBT by mass spectrometry.
Keywords: 2-mercaptobenzothiazole (MBT)